2019
DOI: 10.1590/1806-9282.65.11.1391
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease is associated with a poor outcome at 1-year follow-up after cardiac resynchronization therapy

Abstract: SUMMARY BACKGROUND: Cardiac resynchronization therapy (CRT) is a therapeutic modality for patients with heart failure (HF). The effectiveness of this treatment for event reduction is based on clinical trials where the population of patients with Chagas' disease (DC) is underrepresented. OBJECTIVE: To evaluate the prognosis after CRT of a population in which CD is an endemic cause of HF. METHODS: A retrospective cohort conducted between January 2015 and December 2016 that included patients with HF and left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
5
0
4
Order By: Relevance
“… 768 , 769 Annual all-cause mortality in those two studies ranged from 9.0% to 9.2%. In other three studies, 770 - 772 the survival of patients with CCCD was significantly lower and the percentage of nonresponders to CRT was significantly higher as compared to that of patients with other cardiomyopathies. In patients undergoing CRT, the presence of CCCD increased the risk of death by approximately two to four times.…”
Section: 2 Pacemaker Cardioverter-defibrillator and Cardiac Resynchro...mentioning
confidence: 77%
See 2 more Smart Citations
“… 768 , 769 Annual all-cause mortality in those two studies ranged from 9.0% to 9.2%. In other three studies, 770 - 772 the survival of patients with CCCD was significantly lower and the percentage of nonresponders to CRT was significantly higher as compared to that of patients with other cardiomyopathies. In patients undergoing CRT, the presence of CCCD increased the risk of death by approximately two to four times.…”
Section: 2 Pacemaker Cardioverter-defibrillator and Cardiac Resynchro...mentioning
confidence: 77%
“…Em pacientes submetidos à TRC, a presença de CCDC aumentou o risco de óbito em cerca de 2 a 4 vezes. 770 , 772 …”
Section: 2 Marca-passo Cardioversor-desfibrilador E Ressincronizadorunclassified
See 1 more Smart Citation
“…Simirlaly, Passos, et al also demonstrated a worse prognosis in combined events in patients with Chagas cardiomyopathy after CRT. 7,8 It is important to emphasize that, since intrinsic LBBB in Chagas heart disease is uncommon, and it is considered an arrhythmogenic cardiomyopathy characterized by a wide variety of abnormalities of the conduction, it is expected a higher incidence of upgraded-CRT implantation in this patients. In fact, in the cohort presented by Martinelli et al, there was a 73.9% incidence of induced-LBBB in Chagas' disease patients undergoing CRT.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that CD patients had a worse prognosis compared to other HF etiologies, and recent studies suggests that these patients also have a higher short-term mortality rate after CRT. 7,8 As the need for a pacemaker implantation is common in the course of CD cardiomyopathy, and since LBBB is relatively rare in this patients, an expected higher incidence of upgrade-CRT implantation in this population might play a role in worsening the outcomes. Thus, the aim of this study is to compare the short-term mortality between upgrade and de Novo-CRT implantation in a heart failure population where Chagas disease is endemic.…”
Section: Introductionmentioning
confidence: 99%